Prediction of bronchodilation test in adults with chronic cough suspected of cough variant asthma - Hao, Huijuan; Pan, Yilin; Xu, Zichong; Xu, Zengchao; Bao, Wuping; Xue, Yishu; Lv, Chengjian; Lin, Jingwang; Zhang, Yingying; Zhang, Min (Frontiers in Medicine, 2022)
Background: Cough variant asthma (CVA) is underdiagnosed and undertreated due to the atypical symptoms, low diagnostic sensitivity of bronchodilation test (BDT), and limited application of bronchial challenge test. Objective: To investigate whether airway reversibility in BDT can predict CVA diagnosis in patients with chronic cough and negative BDT. Methods: This open-label, prospective cohort study included patients with chronic cough, nearly normal chest CT scan, and negative BDT results. Inhaled corticosteroids and long-acting ꞵ2 agonists were given for 4 weeks. Confirmed diagnosis of CVA was defined as remarkably improved symptoms and an increase of forced expiratory volume in 1 second (FEV1) by >12% and >200 mL from baseline after 4 weeks of treatment. Results: Of 155 patients recruited, 140 completed the study. Patients in the CVA positive diagnosis group had lower baseline spirometry indices as FEV1, and forced expiratory flows (FEFs), and greater absolute (∆) and percent (∆%) improvements in FEV1 and FEFs, and also had higher fractional exhaled nitric oxide (FENO) than in the CVA negative diagnosis group. The receiver operating characteristic curves (AUCs) of ∆FEV1%, FEF25-75%pred (percentage of predicted forced expiratory flow at 25% to 75%), and FENO for CVA diagnosis was 0.825, 0.714, and 0.637, with cutoff values of 5.90%, 61.99%, and 41.50 ppb, respectively. A joint model of ∆FEV1% combined with FEF25-75%pred or FENO increased the AUC to 0.848 and 0.847, respectively. Conclusions: ∆FEV1% in BDT can predict a CVA diagnosis and response to anti-asthma treatment in patients with chronic cough and negative BDT.